2007
DOI: 10.1007/s10334-007-0092-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimized spectrally selective steady-state free precession sequences for cartilage imaging at ultra-high fields

Abstract: Object Fat suppressed 3D steady-state free precession (SSFP) sequences are of special interest in cartilage imaging due to their short repetition time in combination with high signal-to-noise ratio. At low-to-high fields (1.5-3.0 T), spectral spatial (spsp) radio frequency (RF) pulses perform superiorly over conventional saturation of the fat signal (FATSAT pulses). However, ultra-high fields (7.0 T and more) may offer alternative fat suppression techniques as a result of the increased chemical shift. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The prominent reverse change in signal from fat (as indicated by the white arrows in Fig. 8a) relates to the spatial spectral selectivity of the RF pulse (8), which becomes at low fields only apparent for considerable pulse durations (T RF ϳ 8 ms).…”
Section: Discussionmentioning
confidence: 98%
“…The prominent reverse change in signal from fat (as indicated by the white arrows in Fig. 8a) relates to the spatial spectral selectivity of the RF pulse (8), which becomes at low fields only apparent for considerable pulse durations (T RF ϳ 8 ms).…”
Section: Discussionmentioning
confidence: 98%
“…Binomial water excitation pulses have been proven to be beneficial for cartilage imaging (17), where uniform fat suppression with high spatial resolution is required. Cartilage imaging with single frequency selective RF pulses at ultrahigh‐fields has been shown to be easily applicable for fat suppression or fat–water separation (18).…”
Section: Spatial‐spectral Pulses (Water Excitation)mentioning
confidence: 99%
“…2), but this has to be traded off for a loss of signal intensity. However, the increased chemical shift differences between water and fat at ultra-high fields can also be used; a recent study has shown that it might be used for optimized fat suppression purposes 7 or spectroscopy applications. 8 Another important issue at 7.0 T is that the regulatory limitations for specific SARs should not be exceeded, although RF power deposition is much higher than at 1.5 T or 3.0 T, due to its quadratic dependence on B 0 ; this is especially true for high-duty RF pulse sequences in three-dimensional (3D) mode.…”
Section: Mr Scanner and Radiofrequency Coilmentioning
confidence: 99%